Simona Șimon, Claudia E. Stoian, Anca Dejica-Carțiș, Andrea Kriston. 2018. A Multilingual Dictionary of Education: English-German-French-Romanian. Szeged: JATE Press, ISBN 978 963 315 375 8, pp. 214 - Marcela Alina FĂRCAȘIU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
Book review